Earth Beings Ecologies of Practice across Andean Worlds - de la Cadena, Marisol (Duke University Press, 2015)
Earth Beings is the fruit of Marisol de la Cadena's decade-long conversations with Mariano and Nazario Turpo, father and son, runakuna or Quechua people. Concerned with the mutual entanglements of indigenous and nonindigenous worlds, and the partial connections between them, de la Cadena presents how the Turpos' indigenous ways of knowing and being include and exceed modern and nonmodern practices. Her discussion of indigenous political strategies-a realm that need not abide by binary logics-reconfigures how to think about and question modern politics, while pushing her readers to think beyond "hybridity" and toward translation, communication that accepts incommensurability, and mutual difference as conditions for ethnography to work.